Serrated polyposis syndrome; epidemiology and management. (June 2022) - Carballal, S.; Balaguer, F.; IJspeert, J.E.G.
Abstract: Serrated colorectal polyps, long considered innocent, are currently recognized as the precursors to one-third of all colorectal cancers (CRC). Serrated polyposis syndrome (SPS), characterized by accumulation of multiple and/or large serrated polyps, symbolizes the highest expression of serrated pathway of carcinogenesis, leading to a high risk of CRC when it is not detected or treated on time. Although previously considered uncommon, SPS is now acknowledged as the most prevalent colorectal polyposis. This syndrome has attracted increasing interest over the past decade and has become a hot topic in the field of gastrointestinal oncology. Besides a small proportion of cases caused by germline mutations in RNF43, no clear genetic cause has been identified. Both epigenetic and environmental factors, especially smoking, have been related to this syndrome, but the etiology of SPS remains uncertain and diagnosis is based on endoscopic criteria. Recent studies on SPS have focused on identifying the underlying risk-factors for CRC, defining the best endoscopic techniques for surveillance and establishing optimal preventive strategies aimed at reducing CRC-incidence without exposing patients to unnecessary procedures. The purpose of this chapter is to review, from a practical perspective, current knowledge and future directions in the diagnosis and management of serrated polyposis syndrome.